Correlation between Tumor Location and Size in Intracranial Tumor Patients and Seizure Types - Kurniawan Ritonga, Ilham; Kemala Nasution, Irina; Muhammad Iqbal, Kiki (Journal of Society Medicine, 2024)
Introduction: Brain tumors are rare with a worldwide incidence of 296,851 cases worldwide. A large tumor size indicates a long duration of silent growth, allowing more time for seizures to develop. The aim of this study was to determine the correlation between tumor location and size in patients with intracranial tumors and the type of seizure. Methods: This study used a cross-sectional design in patients who encountered seizure and had been diagnosed with intracranial tumors undergoing treatment at H. Adam Malik Hospital Medan We used Fisher Exact analysis test to determine the relationship of seizure generation type in intracranial tumor patients based on tumor location and Chi-Square analysis test to determine the relationship of seizure generation type in intracranial tumor patients based on tumor size. This study included 43 patients with intracranial tumors accompanied by seizures. Results: Statistical analysis showed insignificant results between tumor location and type of seizure with  p value of 0.543 was obstained, indicating that the relationship between tumor location and type of seizure was not significant (p < 0.05). The results of statistical analysis showed a significant result between tumor size and type of seizure with p value of 0.048. Conclusion: There was no association between tumor location in intracranial tumor patients and the type of seizure. However, there was a relationship between tumor size in intracranial tumor patients and the type of seizure.